A Multicenter Evaluation of the Performance and Usability of a Novel Glucose Monitoring System in Chinese Adults With Diabetes. (March 2017) - Ji, Linong; Guo, Xiaohui; Guo, Lixin; Ren, Qian; Yu, Nan; Zhang, Jie
Objective: Flash glucose monitoring is a new glucose sensing technique that measures interstitial glucose levels for up to 14 days and does not require any calibration. The aim of this study is to evaluate the performance of the new system in Chinese patients with diabetes. Methods: A multicenter, prospective, masked study was performed in a total of 45 subjects with diabetes. Subjects wore 2 sensors at the same time, for up to 14 days. The accuracy was evaluated against capillary blood glucose (BG) and venous Yellow Springs Instrument (YSI; Yellow Springs, OH) measurements. During all 14 days, subjects were asked to perform at least 8 capillary BG tests per day. Each subject attended 3 days of 8-hour clinic sessions to measure YSI and sensor readings every 15 minutes. Results: Forty subjects had evaluable glucose readings, with 6687 of 6696 (99.9%) sensor and capillary BG pairs within consensus error grid zones A and B, including 5824 (87.0%) in zone A. The 6969 sensor and venous YSI pairs resulted in 6965 (99.9%) pairs within zones A and B, including 5755 (82.6%) in zone A. The sensor pairs with BG and YSI result in mean absolute relative difference (MARD) of 10.0% and 10.7%, respectively. Overall between-sensor coefficient of variation (CV) was 8.0%, and the mean lag time was 3.1 (95% confidence interval 2.54 to 4.29) minutes. Conclusions: The system works well for people with diabetes in China, and it is easy to wear and use.